Ashford Gallery Emerging Artists 2004. - Exhibition. Ashford Gallery Emerging Artists 2004. Ashford Gallery Dublin. 2004-10-01. 2004-10-21 (Dublin : Ashford Gallery Dublin, 2004)
Swords, Mark ; Martin, Niall ; Cunningham, Padraig ; Melvin, Sheila ; Thorpe, Cara ; Wilson, Keith ; Beattle, John ; Chan, Patricia ; Lynott, Anne ; Cregg, Martin ; Dowling, Fiona ; Halliday, Angela ; Hunter, Jonathan
Engels
boek